2011
DOI: 10.1167/iovs.09-4493
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography May Be Used to Predict Visual Acuity in Patients with Macular Edema

Abstract: This study showed that the cross-sectional area of retinal tissue between the plexiform layers in cystoid macular edema, as imaged by OCT, is the best indicator of visual function at baseline. Further prospective treatment trials are needed to investigate this parameter as a predictor of visual outcome after intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
112
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(120 citation statements)
references
References 27 publications
4
112
2
2
Order By: Relevance
“…When considering the CMT, the mean difference between baseline and 12 months was similar for the two groups (pre-treated group: 205 μm, naïve group: 173 μm). In agreement with other studies, [17][18][19] this finding points to the complex relationship between VA and CMT, implying that simply reducing oedema does not guarantee improvement in visual function. Concurring with DRCRnet study, results from ADMOR imply that patients who had received previous treatments for DMO can still benefit from ranibizumab injections.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…When considering the CMT, the mean difference between baseline and 12 months was similar for the two groups (pre-treated group: 205 μm, naïve group: 173 μm). In agreement with other studies, [17][18][19] this finding points to the complex relationship between VA and CMT, implying that simply reducing oedema does not guarantee improvement in visual function. Concurring with DRCRnet study, results from ADMOR imply that patients who had received previous treatments for DMO can still benefit from ranibizumab injections.…”
Section: Discussionsupporting
confidence: 92%
“…Although greater numbers are required for statistical analysis of this heterogeneous group, these findings agree with other studies that have investigated the relationship between OCT-measured CMT and VA in DMO. [17][18][19] Results show a weak to modest correlation, with at times unpredictable reduction of VA with decrease in CMT. 18 Better understanding of the anatomical changes depicted on OCT is required to specifically assess neuronal survival, which can then be better correlated with VA. 19 Looking at the baseline structure as a predictor for outcome, ADMOR found that the mean baseline VA in eyes with a thinner CMT (55.2 ± 13.4) was not significantly different to the baseline VA of eyes with a thicker CMT (53.8 ± 12.7) (unpaired t-test P = 0.07).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, a recent study showed that the cross-sectional area of retinal tissue between the plexiform layers in CMO on OCT is the best indicator of visual function. 28 This observation may also be explained by the fact that DRT may represent the milder form of oedema characterised by intracytoplasmic swelling of Muller cells, 29 whereas cystoid spaces result from liquefaction necrosis of Muller cells explaining the poor resolution to treatment. 30 The number of SRDs in our case series was very small to assess its predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic or severe MO may lead to temporary or permanent visual loss depending on the degree of strain or disruption of the microscopic intraretinal neural connections (transmission defects) and the intracellular damage suffered by the visual elements (transduction defects). 1 Steroids inhibit the formation of both prostaglandins and leukotrienes and decrease intracellular and extracellular oedema by suppression of macrophage activity, vasoconstrictive effect, reduction of lymphokine production, 2 and downregulation of production of vascular endothelial growth factor (VEGF). 3 Several randomized clinical trials have reported good short-term efficacy data on intravitreal triamcinolone acetonide both in terms of improving visual acuity and reducing central retinal thickness (CRT) in patients with MO because of various retinal vascular diseases.…”
Section: Introductionmentioning
confidence: 99%